PENYEDIAAN AIR BERSIH BERBASIS KELEMBAGAAN DAN MASYARAKAT Studi Kasus Di Kepulauan Pangkajene, Sulawesi Selatan - Herlambang, Arie (Center for Environmental Technology, 2007)
Pangkep Island consist of 117 Island, situated in Southwest Makasar City, South Sulawesi. These islandsÃ‚Â supply Ã‚Â fish and other marine commodityÃ‚Â to the people who lives in nearby town. Unfortunately, they always lack of water, especially at the long dry season. Ã‚Â Usually at rainy season, they collect water from the roof tileÃ‚Â toÃ‚Â storage tank. But at the long dry season the reserve water in not enough to fulfill daily needs. So it is necessary to applied some technology to create fresh water in some island. Ã‚Â One of Island that has chosen as a pilot project is Pandangan Island. Pandangan Island can be achieved from Pangkep City only five hours using tradisional ship. The population around 1200 people and most of them are fisherman. At the long dry season they always lack of fresh water. The reverse osmosis system, capacity 10 m3/day, has been chosen as technology to overcome water problem in Pandangan Island. For remote area, it is assume only 5 liter/day/capita is enough, so the system could fulfill up to 2000 people. The equipment installed in the central Island, using shallow well as a intake water. The efficiency salt reduction is 95 Ã¢â‚¬â€œ 98% and recovery ratio 15 Ã¢â‚¬â€œ 35%. Ã‚Â The establishment of committee is important to manage operasional of reverse osmosis system. Committee usually consist of 2 technical person and 1 management person, and they come from local people and well train, beside they also should have ability to sell the product water to surrounding island with competitive price. Ã‚Â Ã‚Â ItÃ¢â‚¬â„¢s need big effort to build sea water treatment in each island, so the priority should be determined, especially for crowded, populated and remote island such as Pandangan.Ã‚Â Kata Kunci : Air bersih, kelembagaan, pengolahan air laut.